Numerical Validation of Long-Term Behaviour of Reinforced Recycled Aggregate Concrete Beam - Abdulmajed Dalia Alaa Aldeen; Daud Sultan Ahmed; Alrshoudi Fahed (Civil and Environmental Engineering)
This research presents an advanced computational framework for predicting long-term deflection, crack width, and creep recovery in reinforced concrete beams incorporating recycled aggregate. The study employs a sophisticated nonlinear finite element analysis using Diana FEA software to construct three distinct models based on widely adopted design codes, i.e., Eurocode 2 EN 1992-1-1, fib Model Code (2010), and ACI 209R-92. The numerical models were rigorously validated through comparative analysis with extant experimental data, with a specific focus on examining the effects of creep, shrinkage, and loss of tension stiffening on long-term deflection, crack width, and creep recovery. This investigation specifically addresses the calculation of long-term deflection, crack width, and creep recovery in recycled aggregate concrete beams subjected to sustained loading over a 3000-day period. The study findings indicate that the fib Model Code (2010) is the most reliable for predicting long-term deflection, crack width, and recovery phenomena, consistently aligning closely with experimental results. In contrast, Eurocode 2 EN 1992-1-1 tends to overestimate deflections during early loading. While ACI 209R-92 shows lower error percentages initially, it significantly underestimates deflections by the end of the loading period.